Clinical features and outcomes of infective endocarditis in persons experiencing homelessness - Torrance Teng; Kyle Crooker; Tess Hickey; Max HoddWells; Ashwini Sarathy; Sean Muniz; Jennifer Lor; Amy Chang; Bradley J. Tompkins; Aaron O’Brien; Elly Riser; Devika Singh; et al. (Infectious Diseases of Poverty)
Abstract Background Infective endocarditis (IE) is associated with significant morbidity and mortality and current treatment guidelines recommend a prolonged course of intravenous antibiotics. However, individuals experiencing homelessness face greater barriers to standard IE care. The aim of this study was to compare IE characteristics and outcomes in an unhoused population versus a housed population. Methods A retrospective cohort study encompassing 2010–2020 was conducted in Burlington, Vermont, comparing characteristics and outcomes of patients with IE who did or did not experience homelessness at the time of their infection. Primary outcomes included 30-day, 90-day, and 365-day mortality, IE-related mortality, and IE-related readmission rates. Secondary outcomes included rates of microbiologic failure and treatment failure. Results Of 378 included patients with IE, 30 (7.9%) experienced homelessness and 348 (92.1%) did not. The unhoused cohort was more likely to have right-sided IE involving the tricuspid valve (50.0% vs 21.6%, P = 0.006) and for the causative organism to be methicillin-resistant Staphylococcus aureus (MRSA) [9 (30.0%) vs 43 (12.4%), P = 0.039]. Mortality, IE-related mortality, and IE-related readmission rates were not significantly different between groups at any time point measured. For secondary outcomes, differences in microbiologic failure [5 (16.7%) vs 36 (10.3%), P = 0.543] and treatment failure [9 (30.0%) vs 105 (30.2%), P = 1.000] were also not statistically significant. Conclusions Future research should elucidate factors that entail increased risk of poor outcomes in this important underserved population and how to best mitigate them.